Respostas

2014-04-23T13:55:26-03:00
4)
h)  \frac{4a-2}{3} = \frac{5.(a+3)}{2}

 \frac{4a-2}{3} = \frac{5a+15}{2}

15a+45=8a-4

15a-8a=-4-45

7a=-49

a= \frac{-49}{7}

a=-7

i)  \frac{3x}{2} +2=3x-2

3x +4=6x-4

3x-6x =-4-4

-3x =-8

x= \frac{-8}{-3}

x= \frac{8}{3}

j)  \frac{2x-3}{4} + \frac{x-1}{2} = \frac{5-x}{2}

 \frac{2x-3}{4} + \frac{2.(x-1)}{4} = \frac{2.(5-x)}{4}

2x-3+ 2.(x-1) = 2.(5-x)

2x-3+ 2x-2 = 10-2x

4x-5 = 10-2x

4x+2x = 10+5

6x = 15

x= \frac{15}{6}

x= \frac{5}{2}

k)  \frac{x+2}{3} - \frac{4-5x}{2} = \frac{3x-5}{4} + \frac{1}{3}

 \frac{4.(x+2)}{12} - \frac{6.(4-5x)}{12} = \frac{3.(3x-5)}{12} + \frac{4}{12}

4.(x+2) -6.(4-5x) = 3.(3x-5) + 4

4x+8 -24+30x= 9x-15 + 4

34x-16= 9x-11

34x- 9x=-11+16

25x=5

x= \frac{5}{25}

x= \frac{1}{5}